'Three raindrops and some dust': combining archival and GIS analysis to map the spatial distribution of the impact of the Federation Drought of 1895–1903 in rural New South Wales. (January 2017) - Tierney, Robert; Parton, Kevin A.; Duffy, Deanna
Abstract: Stories abound about the devastating effects of Australia's Federation Drought during the early years of the twentieth century. The aim of this paper is to enhance understanding of what is widely regarded as one of the worst droughts on record in Australia by analysing its differentiated spatial impacts across rural New South Wales (NSW). Newspaper articles from the period are first used to provide a spatial disaggregation that suggests varying impacts of the drought by region. In many instances these articles also present a more human narrative of the challenges for those on the land. The paper then investigates the spatial differences further using archival and quantitative methods. First, county-level data on wheat production from the NSW Statistical Register have been assembled. These data facilitated the assessment of the spatial impact of the drought by generating a drought index for each of the forty-three counties, from which a contour map has been produced. Second, statistical information has been collected from the Annual Reports of the NSW Railway Commissioners which recorded wheat cargoes across the state's inland regional rail network. This in turn enabled assessment of the spatial impact of the drought by means of a second contour map based on ninety-one railway stations. In combination, these methods provide a richer picture, and a more detailed and precise understanding of the uneven geography of the Federation Drought of 1895–1903. Highlights: Demonstrates that the impact of the Federation Drought of New South Wales differed by location. Shows that the regions suffering least tended to have fortunate rainfall events. Argues that in some areas the hostile climate confronted new settlers. Combines archival and GIS methods to produce synergistic insights. Concludes that the drought had minor lasting impact on the development of the wheat-sheep belt.